Profile, prevalence and perception of high school students about the practice of self-medication (Research, Society and Development, 2022)
Self-medication is considered a widespread practice in the world, associated with the indiscriminate use of medicines. Such conduct is a health risk, especially when practiced by school-aged individuals. Thus, the objective of the present study was to evaluate the profile, prevalence and perception of high school students about the practice of self-medication. For this, a cross-sectional, descriptive study was carried out with 270 students from a high school reference school. A structured questionnaire on behaviors and procedures related to self-medication was applied. There was a prevalence in the age group from 19 to 22 years (46.6%), in female individuals (62.9%). Among the drugs mentioned, analgesics prevailed (78.1%), 98.1% do not read the package insert before taking medication and 70.6% consume the same medication in cases of recurrence. Therefore, it is concluded that it is extremely important to raise awareness about the rational use of medicines among students.